2019
DOI: 10.1021/acsanm.9b00348
|View full text |Cite
|
Sign up to set email alerts
|

Amino-Functionalized Graphene Oxide for the Capture and Photothermal Inhibition of Bacteria

Abstract: Amino-functionalized graphene oxide (GO-NH2) was prepared for enhanced antibacterial properties through excellent photothermal efficiency. This nanosheet could easily target the bacterial surface through electrostatic attraction. Upon white light irradiation, GO-NH2 with superior antibacterial efficacy could inhibit the growth of Gram-negative and Gram-positive bacteria, resulting in an increase to 32-times more than the antibacterial activity of GO alone. Through studies of the antibacterial mechanism, it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 41 publications
0
29
0
3
Order By: Relevance
“…此外, 通过将乙二胺四乙酸 [57] 、对苯二 胺 [48] 、 甘氨酸 [58] 等共价键合的方式也可以在 GO 表面引 入氨基. 由于细胞膜通常带有负电, 氨基化可以增加 GO 表 面的正电荷密度, 从而增强 GO 对细菌的捕获能力 [59] . 同时, GO-NH 2 可以有效地破坏细菌的细胞膜, 进而造 成细胞质的流失, 实现杀菌的目的 [59] .…”
Section: 羧基化unclassified
See 2 more Smart Citations
“…此外, 通过将乙二胺四乙酸 [57] 、对苯二 胺 [48] 、 甘氨酸 [58] 等共价键合的方式也可以在 GO 表面引 入氨基. 由于细胞膜通常带有负电, 氨基化可以增加 GO 表 面的正电荷密度, 从而增强 GO 对细菌的捕获能力 [59] . 同时, GO-NH 2 可以有效地破坏细菌的细胞膜, 进而造 成细胞质的流失, 实现杀菌的目的 [59] .…”
Section: 羧基化unclassified
“…由于细胞膜通常带有负电, 氨基化可以增加 GO 表 面的正电荷密度, 从而增强 GO 对细菌的捕获能力 [59] . 同时, GO-NH 2 可以有效地破坏细菌的细胞膜, 进而造 成细胞质的流失, 实现杀菌的目的 [59] . 与原始态 GO 相 比, GO-NH 2 对金黄色葡萄球菌(Staphylococcus aureus) 和大肠杆菌(Escherichia coli)的抗菌活性分别提高了 16 和 32 倍 [59] .…”
Section: 羧基化unclassified
See 1 more Smart Citation
“…Besides being an essential constituent in biosensor fabrication, graphene also demonstrates interesting properties for the biomedical domain. Inhibition of bacterial proliferation can be achieved with GBNs. For example, Faria et al showed that oxidative debris, which are adsorbed molecules at the surface of GO, are the main culprits for the antimicrobial activity observed with (impure) GO . GBNs have also been used in photothermal constructs that provoke cellular death upon absorption of light. , Such nanomaterials can also be used as biocompatible adhesives suitable for in vivo applications .…”
mentioning
confidence: 99%
“…Inhibition of bacterial proliferation can be achieved with GBNs. For example, Faria et al showed that oxidative debris, which are adsorbed molecules at the surface of GO, are the main culprits for the antimicrobial activity observed with (impure) GO . GBNs have also been used in photothermal constructs that provoke cellular death upon absorption of light. , Such nanomaterials can also be used as biocompatible adhesives suitable for in vivo applications . Finally, GBNs can also be used in the context of drug delivery. , Thus, GO conjugated with folic acid loaded with camptothecin, an antitumor drug, was shown to be internalized by cells and to provoke cell death in all cells that were tested …”
mentioning
confidence: 99%